Biomanipulação experimental como forma de melhoramento da qualidade da água e os seus efeitos na comunidade zooplanctônica - Medeiros, Ana Maria Alves de (2013)
The Order Cladocera is amongst the most studied scientific groups on continental aquatic environments, given that they provide valuable information regarding energy transfer between trophic levels. Cladocerans play important ecological roles by serving as food for higher predators (invertebrates and vertebrates) and by regulating the biomass of freshwater phytoplankton. This study aimed to evaluate the influence of vertebrate predators on Ceriodaphnia cornuta using laboratory experiments. The influence of potential predators on C. cornuta was experimentally tested based on density comparisons along five days (2-day interval between analyses) in the presence of two vertebrate predators, namely, the Nile Tilapia (Oreochromis niloticus, Cichlidae) and the Twospot astyanax (Astyanax bimaculatus,Characidae). C. cornuta individuals remained permanently isolated from predators by a 45 μm mesh size net during the experiment and, therefore, predation rates were not accounted for throughout the study. Furthermore, fertility rate and size were also evaluated alongside with density of C. cornuta and environmental variables sampled included water temperature, pH and dissolved oxygen. Results revealed a higher adult mortality on the former experimental days (due to acclimation or age). Further C. cornuta density increased on both predator treatments (O. niloticus and A. bimaculatus), but was fairly higher on the control treatment (no predators; 5th day). Fertility rate increased on the last experiment days on both predator treatments. Higher body size values were also observed on the last experiment days of the control treatment. Results of the present study suggest that, in the absence of vertebrate predators, C. cornuta showed a somewhat higher population growth and larger body size.